MCM3 promotes hepatocellular carcinoma progression via Epithelial-mesenchymal Transition through AKT/Twist signaling pathway - Wei-Guo Tang; Jin-Feng Feng; Xian Li; Qi-Man Sun; Jin-Wu Hu; Xiao-Lu Ma; Yan-Yan Nie; Yang Xu; Jian Sun; Qi-Meng Chang (Annals of Hepatology)
Introduction and Objectives: Hepatocellular carcinoma (HCC), a leading cause of cancer fatalities, challenges clinicians with high recurrence and metastasis rates, urging the need for novel prognostic markers and therapeutic avenues. Minichromosome maintenance complex component 3 (MCM3) has been implicated in various cancers, but its role in HCC is not well-characterized. Materials and Methods: We investigated MCM3 expression in HCC through cell line and patient sample analyses, functional assays to determine its effect on cellular behaviors, and signal pathway exploration. Results: Elevated MCM3 expression was identified in both HCC cell lines and patient tissues, correlating with microvascular invasion, advanced cancer stage, and reduced survival. Functionally, MCM3 fueled HCC cellular proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) in vitro and expedited tumor growth in vivo. Mechanistically, MCM3 was found to potentiate EMT by upregulating Twist via the AKT signaling pathway. Conclusions: MCM3 emerges as an oncogenic influencer in HCC, driving disease progression through the AKT/Twist axis. Its expression patterns hold prognostic value, and targeting MCM3 may offer a novel therapeutic strategy for HCC.